The Influence of Company Growth, Profitability, Audit Tenure, and Size of Public Accounting Firms on the Acceptance of Going Concern Audit Opinions - Djoko Djoko; Lia Dama Yanti (Komunitas Dosen Indonesia, 2019)
This study aims to obtain empirical evidence regarding the effect of company growth, profitability, audit tenure, and the size of the public accounting firm on the acceptance of going-concern audit opinion. The population in this study is audited financial statements in the basic industrial and chemical manufacturing companies listed on the Indonesia Stock Exchange in 2014-2017. The determination of the sample was done using purposive sampling with a total sample of 43 companies over a period of 4 consecutive years of observation so that the total sample was 172. The data of this study used SPSS version 25 with descriptive statistical tests, logistic regression tests. The results of the research that has been processed show that the significant value of company growth proxied using PP (sales growth) is 0.314, the significant value of profitability that is proxied using ROA is 0.001, the significant value of audit tenure is proxied using AT, which is 0.034 and the proximate KAP size is proxied use UKAP which is 0.977. The results showed that the growth of the company and the size of the public accounting firm did not significantly influence the acceptance of the going concern audit opinion while profitability and audit tenure had a significant effect on the acceptance of the going-concern audit opinion.